1993
DOI: 10.1016/0014-5793(93)80635-8
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of DNA in P388D1 macrophages exposed to oxidised low‐density lipoprotein

Abstract: Exposing a macrophage‐like murine cell line to copper‐oxidised low‐density lipoprotein led to DNA fragmentation which was inhibited by the putative Ca2+/Mg2+ endonuclease inhibitor, zinc sulphate. DNA fragmentation preceded loss of membrane impermeability. These results suggest that apoptosis may be a mechanism of macrophage foam cell death in atherosclerotic lesions in the arterial wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Indeed, oxidised LDL is known to be cytotoxic to a variety of cell types including endothelial cells, smooth muscle cells, macrophages and lymphocytes [9][10][11][12][13]. We have shown using LDL oxidised to defined extents that LDL containing the maximum level of lipid hydroperoxides (LOOH), termed moderately-oxidised LDL, can induce apoptosis in human umbilical artery smooth muscle cells, whereas native LDL does not [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, oxidised LDL is known to be cytotoxic to a variety of cell types including endothelial cells, smooth muscle cells, macrophages and lymphocytes [9][10][11][12][13]. We have shown using LDL oxidised to defined extents that LDL containing the maximum level of lipid hydroperoxides (LOOH), termed moderately-oxidised LDL, can induce apoptosis in human umbilical artery smooth muscle cells, whereas native LDL does not [14].…”
Section: Introductionmentioning
confidence: 99%
“…Quinn and co-workers have shown that oxidised LDL induces chemotaxis in human monocytes, with lysophosphatidyl choline being one of its active components [3,4]. Further, oxidised LDL has been shown to be toxic for a variety of cell types including smooth muscle cells, fibroblasts [5] and more recently mouse peritoneal macrophages [6,7], the macrophage-like cell line P388D1 [8] and human monocyte-macrophages [9]. However, oxidised LDL is a complex mixture of various components including lipid hydroperoxides, oxysterols and aldehydes [10].…”
Section: Introductionmentioning
confidence: 99%
“…2 Among many other effects, oxidized LDL increases the expression of cellular adhesion molecules and chemokines, 3,4 increases the production of metalloproteinases, 5 which probably destabilize the fibrous caps over advanced lesions, and induces apoptosis in cells. 6 The mechanisms by which LDL is oxidized in atherosclerotic lesions remain uncertain, despite a great deal of work. 7 The oxidation hypothesis of atherosclerosis needs to address the high antioxidant capacity of extracellular fluids.…”
mentioning
confidence: 99%